Proteomic analysis of glycated proteins from streptozotocin-induced diabetic rat kidney - Chougale, Ashok D.; Bhat, Shweta P.; Bhujbal, Swapnil V.; Zambare, Mandar R.; Puntambekar, Shraddha; Somani, Rahul S.; Boppana, Ramanamurthy; Giri, Ashok P.; Kulkarni, Mahesh J. (Molecular Biotechnology, 2012)
Glycation of proteins leading to formation of advanced glycation end products (AGEs) has been considered as one of the important causes of diabetic nephropathy. Therefore, in this study, glycated proteins were detected by anti-AGE antibodies from kidney of streptozotocin-induced diabetic rat showing nephropathic symptoms, by using two dimensional electrophoresis and western blot analysis. These glycated proteins were identified and characterized by using combination of peptide mass finger printing and tandem mass spectrometric approaches. Glycated proteins identified included proteins from metabolic pathways, oxidative stress, cell signaling, and transport. Several of the proteins modified by glycation were involved in glucose metabolism. The extent of glycation was higher in diabetes compared to control, in the glycated proteins that were common to both control and diabetic kidney. Two dimensional electrophoresis proteins profiling of glycated proteins suggest that four of the glycated proteins were significantly up regulated in diabetes.
Keywords: AGE; Diabetes; Glucose toxicity; Nephropathy; Post-translation modification

Purification and characterization of an antioxidant protein (similar to 16 kDa) from Terminalia chebula fruit - Srivastava, Pratibha; Raut, Hema N.; Wagh, Renuka S.; Puntambekar, Hemalata M.; Kulkarni, Mahesh J. (Food Chemistry, 2012)
Terminalia chebula fruit is used as folk medicine in India and Southeast Asia. An antioxidant protein was isolated by bioassay guided fractionation of T. chebula fruit by homogenizing in the citrate phosphate buffer. The isolated protein (TCP-III) obtained from fruit was purified by gel chromatography and preparative HPLC, showed apparent molecular weight of 16 kDa by SDS-PAGE and MALDI-TOF/MS analyses. Amino acid sequence obtained by LC-MSE analysis showed homology with the predicted protein fragments of Populus trichocarpa, putative uncharacterized protein fragments from Oryza sativa and with fragments of 17 kDa thylakoid lumenal protein from Spinacia oleracea. TCP-III exhibited significant radical scavenging in DPPH, NO, H2O2 and ABTS assays. In addition, TCP-III inhibited oxidation of linoleic acid in beta-carotene bleaching assay, reduced ferric ions and chelated ferrous ions. The present finding demonstrates uniquely, for the first time, characterization of an antioxidant protein from T. chebula fruit. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: 16 kDa protein molecule of T. chebula; Antioxidant and free radical scavenging activity; Characterization; Purification; Terminalia chebula fruit

Proteome wide reduction in AGE modification in streptozotocin induced diabetic mice by hydralazine mediated transglycation - Kesavan, Suresh K.; Bhat, Shweta; Golegaonkar, Sandeep B.; Jagadeeshaprasad, Mashanipalya G.; Deshmukh, Arati B.; Patil, Harshal S.; Bhosale, Santosh D.; Shaikh, Mahemud L.; Thulasiram, Hirekodathakallu V.; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Scientific Reports, 2013)
The non-enzymatic reaction between glucose and protein can be chemically reversed by transglycation. Here we report the transglycation activity of hydralazine using a newly developed MALDI-TOF-MS based assay. Hydralazine mediated transglycation of HbA1c, plasma proteins and kidney proteins was demonstrated in streptozotocin (STZ) induced diabetic mice, as evidenced by decrease in protein glycation, as well as presence of hydralazine-glucose conjugate in urine of diabetic mice treated with hydralazine. Hydralazine down regulated the expression of Receptor for Advanced Glycation End products (RAGE), NADPH oxidase (NOX), and super oxide dismutase (SOD). These findings will provide a new dimension for developing intervention strategies for the treatment of glycation associated diseases such as diabetes complications, atherosclerosis, and aging.

Proteomic analysis of protease resistant proteins in the diabetic rat kidney - Bansode, Sneha B.; Chougale, Ashok D.; Joshi, Rakesh S.; Giri, Ashok P.; Bodhankar, Subhash L.; Harsulkar, Abhay M.; Kulkarni, Mahesh J. (Molecular & Cellular Proteomics, 2013)
Glycation induced protein aggregation has been implicated in the development of diabetic complications and neurodegenerative diseases. These aggregates are known to be resistant to proteolytic digestion. Here we report the identification of protease resistant proteins from the streptozotocin induced diabetic rat kidney, which included enzymes in glucose metabolism and stress response proteins. These protease resistant proteins were characterized to be advanced glycation end products modified and ubiquitinated by immunological and mass spectrometry analysis. Further, diabetic rat kidney exhibited significantly impaired proteasomal activity. The functional analysis of identified physiologically important enzymes showed that their activity was reduced in diabetic condition. Loss of functional activity of these proteins was compensated by enhanced gene expression. Aggregation prone regions were predicted by in silico analysis and compared with advanced glycation end products modification sites. These findings suggested that the accumulation of protein aggregates is an inevitable consequence of impaired proteasomal activity and protease resistance due to advanced glycation end products modification. Molecular & Cellular Proteomics 12: 10.1074/mcp.M112.020651, 228-236, 2013.

Proteomic profiling and interactome analysis of ER-positive/HER2/neu negative invasive ductal carcinoma of the breast: towards proteomics biomarkers - Korwar, Arvind M.; Bhonsle, Hemangi S.; Ghole, Vikram S.; Gawai, Kachru R.; Koppikar, Chaitanyananda B.; Kulkarni, Mahesh J. (OMICS-A Journal of Integrative Biology, 2013)
Breast cancer, especially ER positive/HER2/neu negative IDC, is the predominant subtype of invasive ductal carcinoma. Although proteomic approaches have been used towards biomarker discovery in clinical breast cancer, ER positive/HER2/neu negative IDC is the least studied subtype. To discover biomarkers, as well as to understand the molecular events associated with disease progression of estrogen receptor positive/HER2/neu negative subtype of invasive ductal carcinoma, differential protein expression profiling was performed by using LC-MSE (MS at elevated energy). A total of 118 proteins were identified, of which 26 were differentially expressed. These identified proteins were functionally classified and their interactions and coexpression were analyzed by using bioinformatic tools PANTHER (Protein Analysis THrough Evolutionary Relationships) and STRING (Search Tool for the Retrieval of Interacting Genes). These proteins were found to be upregulated and were involved in cytoskeletal organization, calcium binding, and stress response. Interactions of annexin A5, actin, S100 A10, glyceraldehyde 3 phosphate dehydrogenase, superoxide dismutase 1, apolipoprotein, fibrinogen, and heat shock proteins were prominent. Differential expression of these proteins was validated by two-dimensional gel electrophoresis and Western blot analysis. The cluster of these proteins may serve as a signature profile for estrogen receptor positive/ HER2/neu negative subtype.

Proteomic study reveals downregulation of apolipoprotein A1 in plasma of poorly controlled diabetes: a pilot study - Bhonsle, Hemangi S.; Korwar, Arvind M.; Chougale, Ashok D.; Kote, Sachin S.; Dhande, Nitin L.; Shelgikar, Kishore M.; Kulkarni, Mahesh J. (Molecular Medicine Reports, 2013)
Proteomic approaches aid in gaining a better understanding of the pathophysiology of diabetic complications. In view of this, differential protein expression in diabetic plasma samples was studied by a combination of proteomic and western blot analyses. Diabetic plasma samples were categorized based on glycated haemoglobin levels as controlled diabetes (CD; 7-8%), poorly controlled diabetes (PCD; >8%) and non-diabetic control (ND;<6.4%). Two-dimensional electrophoresis and liquid chromatography-mass spectrometry revealed differential expression of proteins including upregulation of fibrinogen and haptoglobin and downregulation of vitamin D binding protein, alpha-1-antitrypsin, transthyretin and apolipoprotein A1 (Apo A1) in diabetic compared with non-diabetic plasma samples. Amongst these proteins, Apo A1 downregulation was prominent in PCD. Downregulation of Apo A1 may serve as an early predictive marker of diabetic complications.
Keywords: biomarker; HbA1c; proteomics

Proteomic analysis of human plasma in chronic rheumatic mitral stenosis reveals proteins involved in the complement and coagulation cascade - Mukherjee, Somaditya; Jagadeeshaprasad, Mashanipalya G.; Banerjee, Tanima; Ghosh, Sudip K.; Biswas, Monodeep; Dutta, Santanu; Kulkarni, Mahesh J.; Pattari, Sanjib; Bandyopadhyay, Arun (Clinical Proteomics, 2014)
Background: Rheumatic fever in childhood is the most common cause of Mitral Stenosis in developing countries. The disease is characterized by damaged and deformed mitral valves predisposing them to scarring and narrowing (stenosis) that results in left atrial hypertrophy followed by heart failure. Presently, echocardiography is the main imaging technique used to diagnose Mitral Stenosis. Despite the high prevalence and increased morbidity, no biochemical indicators are available for prediction, diagnosis and management of the disease. Adopting a proteomic approach to study Rheumatic Mitral Stenosis may therefore throw some light in this direction. In our study, we undertook plasma proteomics of human subjects suffering from Rheumatic Mitral Stenosis (n = 6) and Control subjects (n = 6). Six plasma samples, three each from the control and patient groups were pooled and subjected to low abundance protein enrichment. Pooled plasma samples (crude and equalized) were then subjected to in-solution trypsin digestion separately. Digests were analyzed using nano LC-MSE. Data was acquired with the Protein Lynx Global Server v2.5.2 software and searches made against reviewed Homo sapiens database (UniProtKB) for protein identification. Label-free protein quantification was performed in crude plasma only.

Proteomics of arsenic stress in the gram-positive organism Exiguobacterium sp PS NCIM 5463 - Sacheti, Poonam; Patil, Rajendra; Dube, Ankita; Bhonsle, Hemangi S.; Thombre, Dipalee; Marathe, Sayali; Vidhate, Ravindra; Wagh, Priyanka; Kulkarni, Mahesh J.; Rapole, Srikanth; Gade, Wasudeo N. (Applied Microbiology and Biotechnology, 2014)
The general responses of microorganisms to environmental onslaughts are modulated by altering the gene expression pattern to reduce damage in the cell and produce compensating stress responses. The present study attempts to unravel the response of the Gram-positive Exiguobacterium sp. PS NCIM 5463 in the presence of [As(III)] and arsenate [As(V)] using comparative proteomics via two-dimension gel electrophoresis (2-DE) coupled with identification of proteins using matrix-assisted laser desorption/ionisation (MALDI-TOF/MALDI-TOF/TOF). Out of 926 Coomassie-stained proteins, 45 were differentially expressed (p < 0.05). Considering the resolution and abundance level, 24 spots (peptides) were subjected to MALDI analysis, identified and categorised into several functional categories, viz., nitrogen metabolism, energy and stress regulators, carbohydrate metabolism, protein synthesis components and others. A functional role of each protein is discussed in Exiguobacterium sp. PS 5463 under arsenic stress and validated at their transcript level using a quantitative real-time polymerase chain reaction. Unlike previous reports that unravel the responses toward arsenic stress in Gram-negative organisms, the present study identified new proteins under arsenic stress in a Gram-positive organism, Exiguobacterium sp. PS NCIM 5463, which could elucidate the physiology of organisms under arsenic stress.
Keywords: Arsenic; Exiguobacterium; proteomics; Stress; Transcriptomics

Potential dual role of eugenol in inhibiting advanced glycation end products in diabetes: proteomic and mechanistic insights - Singh, Priyanka; Jayaramaiah, Ramesha H.; Agawane, Sachin B.; Vannuruswamy, Garikapati; Korwar, Arvind M.; Anand, Atul; Dhaygude, Vitthal S.; Shaikh, Mahemud L.; Joshi, Rakesh S.; Boppana, Ramanamurthy; Kulkarni, Mahesh J.; Thulasiram, Hirekodathakallu V.; et al. (Scientific Reports, 2016)
Medicinally important genus Ocimum harbors a vast pool of chemically diverse metabolites. Current study aims at identifying anti-diabetic candidate compounds from Ocimum species. Major metabolites in O. kilimandscharicum, O. tenuiflorum, O. gratissimum were purified, characterized and evaluated for anti-glycation activity. In vitro inhibition of advanced glycation end products (AGEs) by eugenol was found to be highest. Preliminary biophysical analysis and blind docking studies to understand eugenol-albumin interaction indicated eugenol to possess strong binding affinity for surface exposed lysines. However, binding of eugenol to bovine serum albumin (BSA) did not result in significant change in secondary structure of protein. In vivo diabetic mice model studies with eugenol showed reduction in blood glucose levels by 38% likely due to inhibition of alpha-glucosidase while insulin and glycated hemoglobin levels remain unchanged. Western blotting using anti-AGE antibody and mass spectrometry detected notably fewer AGE modified peptides upon eugenol treatment both in vivo and in vitro. Histopathological examination revealed comparatively lesser lesions in eugenol-treated mice. Thus, we propose eugenol has dual mode of action in combating diabetes; it lowers blood glucose by inhibiting a-glucosidase and prevents AGE formation by binding to epsilon-amine group on lysine, protecting it from glycation, offering potential use in diabetic management.

Proteomic insight reveals elevated levels of albumin in circulating immunecomplexes in diabetic plasma - Bhat, Shweta; Jagadeeshaprasad, Mashanipalya G.; Patil, Yugendra R.; Shaikh, Mahemud L.; Regin, Bhaskaran S.; Mohan, Viswanathan; Giri, Ashok P.; Balasubramanyam, Muthuswamy; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Molecular & Cellular Proteomics, 2016)
A Hyperglycemic condition in diabetes promotes formation of advanced glycation end products, which are known to elicit immune response and form complexes with immunoglobulins called circulating immune complexes. To investigate the involvement of advanced glycation end product (AGE)-modified proteins in the elicitation of an immune response, circulating immune complexes were isolated and proteins associated were identified and characterized. Label-free-based mass spectrometric analysis of circulating immune complexes in clinical plasma of prediabetic, newly diagnosed diabetes, and diabetic microalbuminurea revealed elevated levels of serum albumin in the circulating immune complexes, which were also observed to be AGE modified. Further, to examine the role of glycation, circulating immune complexeswere analyzed in the streptozotocin-induced diabetic mice treated with or without aminoguanidine, a prototype glycation inhibitor. Mass spectrometric analysis of circulating immune complexes showed elevated levels of serum albumin in plasma from diabetic mice over that of control animals. Aminoguanidine-treated diabetic mice displayed decreased AGE modification of plasma albumin, accompanied by a reduced level of albumin in the circulating immune complexes. In addition, elevated levels of proinflammatory cytokines such as IL-1b, IL-2, and TNF-alpha were observed in diabetes, which were reduced with aminoguanidine treatment, suggesting the involvement of glycation in the immune response.

Placental proteomics provides insights into pathophysiology of pre-eclampsia and predicts possible markers in plasma - Mary, Sheon; Kulkarni, Mahesh J.; Malakar, Dipankar; Joshi, Sadhana Ramchandra; Mehendale, Savita S.; Giri, Ashok P. (Journal of Proteome Research, 2017)
Pre-eclampsia is a hypertensive disorder characterized by the new onset of hypertension >140/90 mmHg and proteinuria after the 20th week of gestation. The disorder is multi-factorial and originates with abnormal placentation. Comparison of the placental proteome of normotensive (n=25) and pre-eclamptic (n=25) patients by gel-free proteomic techniques, identified a total of 2145 proteins in the placenta of which 180 were differentially expressed (>1.3 fold, p<0.05). Gene ontology enrichment analysis of biological process suggested that the differentially expressed proteins belonged to various physiological processes such as angiogenesis, apoptosis, oxidative stress, hypoxia, placental development, which are implicated in the pathophysiology of pre-eclampsia. Some of the differentially expressed proteins were monitored in the plasma by multiple reaction monitoring (MRM) analysis, which showed an increase in Apolipoprotein AI and AII in gestational week 26-30th (2-fold, p<0.01) while haptoglobin and hemopexin decreased in gestational week 26-30th and 40th week/at delivery (1.8 fold, p<0.01) in pre-eclamptic patients. This study provides a proteomic insight into the pathophysiology of pre-eclampsia. Identified candidate proteins can be evaluated further for the development of potential biomarkers associated with pre-eclampsia pathogenesis.

Patho-physiological evaluation of Duranta erecta for the treatment of urolithiasis - Agawane, S. B.; Gupta, V. S.; Kulkarni, Mahesh J.; Bhattacharya, A. K.; Koratkar, Santosh; Rao, Vankudoth Koteswara (Journal of Ayurveda and integrative medicine, 2018)
Background: Urolithiasis is the third common disorder of the urinary system affecting 10-15% of the general population. In recent years, search for new antilithiatic drugs from natural sources has assumed greater importance. Objectives: This study was performed to investigate the anti-urolithiatic activity of methanolic extract of Duranta erecta leaves by in vitro and in vivo analysis. Materials and methods: The study was designed to determine presence of phytochemicals in D. erecta, its yield in percentage, antioxidant activity against 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and anti-microbial property against few bacteria. In vitro analysis was carried out study anti-urolithiatic property of D. erecta by nucleation assay and synthetic urine assay for inhibition of calcium oxalate and calcium oxalate monohydrate crystals formation. An in vivo experiment was performed on Wistar rats for confirmation of anti-urolithiatic property of D. erecta in animal model. Results: D. erecta has the presence of primary and secondary metabolites like glycoside, saponins, sterols, flavonoids, phenols, tannins, alkaloids, carbohydrates and proteins. Methanolic extract of D. erecta gave a very good yield (60%). D. erecta proved its antioxidant potential by 93.51% inhibition of DPPH radical at a concentration of 1000 μg/mL where ascorbic showed 94.71% of DPPH radical at the same concentration. In vitro tests like nucleation assay and synthetic urine assay showed that D. erecta inhibits formation of calcium oxalate and calcium oxalate monohydrate crystals. It also showed the anti-microbial property by formation of zone of inhibition against few bacteria. An in vivo experiment on Wistar rat animal model confirmed the anti-urolithiatic property of D. erecta L. leaves extract. Conclusions: Based on the results, we reported that D. erecta may treat calcium oxalate crystal deposition in the kidney by preventing hyperoxaluria-induced peroxidative damage to the renal tubular membrane surface (lipid peroxidation). It has anti-microbial potential so it may also inhibit the secondary bacterial infection in kidney. Based on the data, it can be concluded that this herb can be used as a potential anti-urolithiasis agent for kidney stone removal.

Proteomic study of endothelial dysfunction induced by Ages and its possible role in diabetic cardiovascular complications - Banarjee, Reema; Sharma, Akshay; Bai, Shakuntala; Deshmukh, Arati; Kulkarni, Mahesh J. (Journal of Proteomics, 2018)
Endothelial dysfunction is one of the primary steps in the development of diabetes associated cardiovascular diseases. Hyperglycemic condition in diabetes promotes accumulation of advanced glycation end products (AGEs) in the plasma, that interact with the receptor for AGEs (RAGE) present on the endothelial cells and negatively affect their function. Using Human umbilical vascular endothelial cells (HUVECs) in culture, the effect of glycated human serum albumin on global proteomic changes was studied by SWATH-MS, a label free quantitative proteomic approach. Out of the 1860 proteins identified, 161 showed higher abundance while 123 showed lesser abundance in cells treated with glycated HSA. Bioinformatic analysis revealed that the differentially regulated proteins were involved in various processes such as apoptosis, oxidative stress etc. that are associated with endothelial dysfunction. Furthermore, the iRegulon analysis and immunofuorescence studies indicated that several of the differentially regulated proteins were transcriptionally regulated by NF-kappa B, that is downstream to AGE-RAGE axis. Some of the important differentially regulated proteins include ICAM1, vWF, PAI-1 that affect important endothelial functions like cell adhesion and blood coagulation. qPCR analysis showed an increase in expression of the AGE receptor RAGE along with other genes involved in endothelial function. AGE treatment to HUVEC cells led to increased oxidative stress and apoptosis. This is the first proteomics study that provides insight into proteomic changes downstream to AGE-RAGE axis leading to endothelial dysfunction and predisposing to cardiovascular complications. Significance: Cardiovascular disease (CVD) is a major pathological outcome in diabetic patients and it is important to address ways that target its development before the onset. Elevated plasma AGEs in diabetes can affect endothelial function and can continue to show their effects even after blood glucose levels are back to normal. Since endothelial dysfunction acts as one of the initiating factors for the development of CVD, understanding how AGEs affect the endothelial cell proteome to cause dysfunction will provide insight into the mechanisms involved and aid designing new therapeutic approaches.

Possible role of glycation in the regulation of amyloid beta precursor protein processing leading to amyloid beta accumulation - Patil, Gouri V.; Joshi, Rakesh S.; Kazi, Rubina S.; Kulsange, Shabda E.; Kulkarni, Mahesh J. (Medical Hypotheses, 2020)
Alzheimer's disease (AD) is one of the most common forms of neurodegenerative diseases amongst the aged population. The disease is multifactorial, and diabetes has been considered as one of the major risk factors for the development of AD. Chronic hyperglycemic condition in diabetes promotes non-enzymatic protein modification by glucose termed as glycation, which affects protein structure and function. Previous studies have shown that many of the enzymes, including proteases, are affected by glycation. Conversely, glycated proteins are known to become resistant to protease action. In these hypotheses, we have extended these two concepts to the regulation of amyloid-beta protein precursor (A beta PP) by secretases leading to amyloid-beta (Af3) accumulation. The first hypothesis deals with the glycation of alpha-secretases leading to its reduced activity, while in the second hypothesis, A beta PP glycation may prevent a-secretases action, rendering its processing by beta secretase. As diabetes is a risk factor for the development of AD, either or both these pathways may operate, leading to the manifestation of AD.
Keywords: Alpha-secretase; Alzheimer `s disease; Amyloid-beta; Amyloid-beta protein precursor; Beta-secretase; Diabetes; glucose; Glycation; Type-3 diabetes

Proteomic analysis detects deregulated reverse cholesterol transport in human subjects with ST-segment elevation myocardial infarction (vol 222, 103796, 2020) - Das, Apabrita Ayan; Choudhury, Kamalika Roy; Jagadeeshaprasad, M. G.; Kulkarni, Mahesh J.; Mondal, Prakash Chandra; Bandyopadhyay, Arun (Journal of Proteomics, 2020)

Proteomic analysis detects deregulated reverse cholesterol transport in human subjects with ST-segment elevation myocardial infarction - Das, Apabrita Ayan; Choudhury, Kamalika Roy; Jagadeeshaprasad, M. G.; Kulkarni, Mahesh J.; Mondal, Prakash Chandra; Bandyopadhyay, Arun (Journal of Proteomics, 2020)
Reverse cholesterol transport (RCT) plays a critical role in removing cholesterol from the arterial wall. However, very few reports directly relate chronic inflammation and RCT with atherosclerosis. The present study was undertaken to investigate clinical implications of significantly altered circulating proteins in subjects with ST-segment elevation myocardial infarction (STEMI) in the manifestation of atherosclerotic events. Using a casecontrol design, more than 2500 proteins in both STEMI and healthy control subjects were identified by Orbitrap mass spectrometer. Quantitative proteomics study revealed downregulation of 26 proteins while expression of 38 proteins increased significantly in STEMI subjects compared to healthy controls. Pathway enrichment analyses indicated that most of the identified proteins were related to chronic inflammation, atherosclerosis, and RCT. Altered proteins such as AZGP1, ABCA5, Calicin, PGLYRP2, HAVCR2 and C17ORF57 were further validated by Western blotting analysis of human plasma. Pathophysiological significance was studied using macrophage derived foam cell for their critical role in RCT which indicated the imbalance of RCT via the interaction of AZGP1 with CD36. In summary, this study revealed a unique relationship of some novel proteins apparently responsible for impaired RCT and chronic inflammation leading to atherothrombosis and myocardial infarction. Significance: In the present study we identified >= 2500 unique circulating proteins in healthy control and clinically diagnosed STEMI subjects among which 423 proteins were found to be common in both the groups. We further show 64 proteins significantly different between healthy control and STEMI subjects. Proteomic analyses reveal a panel of proteins associated with atherosclerosis and STEMI. One of the proteins, AZGP1, an adipokine, is likely to act as the missing link between chronic inflammation and cholesterol transport. Deregulation of reverse cholesterol transport might be orchestrated by AZGP1, CD36, ABCA5, and PPARy in STEMI subjects. The present study employs shotgun and quantitative proteomics followed by in vitro validations demonstrating a biochemical basis for reverse cholesterol transport in the local milieu of the luminal wall of the artery which are critical for plaque build-up and atherosclerosis.
Keywords: Atherosclerosis; AZGP1; CD36; Plasma proteomics; Reverse cholesterol transport; STEMI

Protriptyline improves spatial memory and reduces oxidative damage by regulating NF kappa B-BDNF/CREB signaling axis in streptozotocin-induced rat model of Alzheimer's disease - Tiwari, Virendra; Mishra, Akanksha; Singh, Sonu; Mishra, Sandeep Kumar; Sahu, Kiran Kumari; Parul; Kulkarni, Mahesh J.; Shukla, Rakesh; Shukla, Shubha (Brain Research, 2021)
Antidepressants are well known to exert their role via upregulation of brain derived neurotrophic factor (BDNF). BDNF has been reported to exerts its neuroprotective effect in rodent and primate models as well as in patients of Alzheimer's disease (AD). The aim of our study was to evaluate the effect of protriptyline (PRT), a tricyclic antidepressant, in streptozotocin (STZ)- induced rat model of AD. Total 10 mu l of STZ was injected into each ventricle (1 mg/kg). PRT (10 mg/kg, i.p.) treatment was started 3-day post STZ administration and continued till 21 days. We found that STZ treatment significantly increased pTau, A beta 42 and BACE-1 expression, oxidative stress and neurodegeneration in hippocampus and cortex of adult rats. STZ induced impairment in spatial learning and retention memory was associated with increased WO and reduced CREB and BDNF expression in cortex and hippocampus. Interestingly, PRT treatment significantly reduced pTau, A beta 42 and BACE-1 levels, neurodegeneration, oxidative stress and glial activation, contributing to the improved spatial learning and retention memory in STZ treated rats. Moreover, PRT treatment significantly improved p-ERK/ERK ratio and enhanced BDNF and CREB levels by reducing NFXB and GFAP expression in STZ treated rats. Our data suggest that impaired NFXB and CREB signaling potentially contribute in AD pathogenesis by elevating oxidative stress and neuroinflammation mediated neurodegeneration. Our study has established protriptyline as a multi target molecule in pre-clinical model of AD and further investigations on PRT like molecules could pave way for further development of effective new treatments in neurodegenerative disorders.
Keywords: Alzheimer's disease; antidepressant; BDNF; Memory; Oxidative stress; Protriptyline

Proteome profile of stress test assessed cardiovascular disease risk-prone diabetic subjects - Patil, Yugendra R.; Tiwari, Shalbha; Unnikrishnan, A. G.; Kulkarni, Mahesh J. (Journal of Cardiovascular Translational Research, 2025)
Cardiovascular disease (CVD) is the leading cause of death in the diabetic population. There is a need for specific predictive markers to assess CVD risk. The present study explored the plasma proteome profile of treadmill test (TMT) assessed diabetic stress test positive (DSTP) and diabetic stress test negative (DSTN) subjects by performing a SWATH-MS-based label-free quantitative mass spectrometry approach to identify differentially expressed proteins (DEPs). CVD-relevant DEPs were further validated using a targeted mass spectrometry approach (MRM-HR). It was observed that CO4B, PON1 and LUM exhibited considerable differential expression in both the MS approaches, and ROC analysis showed significant AUC (0.97, 0.79 and 0.77, respectively). Overall, the present study reports these proteins as potential alternative markers for TMT in assessing CVD risk. These markers can possibly overcome the limitations of TMT with further validation in the large cohort.Graphical AbstractAn overview of experimental approaches used in the current study. The study design depicts diabetic subjects assessed for cardiovascular risk by TMT or stress test. The experimental design shows the use of the SWATH-MS approach to identify differentially expressed proteins and validate CVD-related proteins with targeted MS approaches such as MRM-HR. Finally, CO4B, PON1 and LUM exhibited significant AUC in ROC analysis, indicating their potential marker capabilities to predict CVD in diabetic subjects.
Keywords: cardiovascular disease; Diabetes; Multiple reaction monitoring; Plasma markers; Proteome profile; Quantitative mass spectrometry